Evaluasi Kinerja Pegawai Pada Kantor Kecamatan Banjar - Mela Meilawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This artichle is entitled: EMPLOYEE PERFORMANCE EVALUATION IN BANJAR DISTRICT OFFICE, BANJAR CITY, which aims to determine the weaknesses and strengths of employee performance at the Banjar District Office, as well as to describe the work process based on employee performance indicators included in this thesis. Employee performance evaluation is carried out periodically, which is an effort to improve employee performance deficiencies and strengths so that employee performance becomes optimal. Evaluation of employee performance is also a motivation for employees to continue to improve skills and develop productivity at work so that they can meet predetermined work standards. Employee performance evaluation is one of the drivers of increasing employee human resources through employee performance evaluation. So in this way employee human resources can continue to increase accompanied by continuously better performance in order to achieve the objectives of the Banjar District Office, Banjar City. This study uses qualitative methods to determine the search, collection and processing and analysis of data. This qualitative research is descriptive in nature, namely explaining events or activities at the time of research or actual. By describing, describing, recording, analyzing, interpreting events and facts into research results. The results of the study show that employee performance evaluation has been carried out routinely through SKP (Employee Performance Targets). Thus so far, the evaluation itself has been running effectively and quickly